Prognostic factors of second hematopoietic allogeneic stem cell transplantation among hematological malignancy patients relapsed after first hematopoietic stem cell transplantation: A single center study - Lu, Yue; Zhang, Jian-Ping; Zhao, Yan-Li; Xiong, Min; Sun, Rui-Juan; Cao, Xing-Yu; Wei, Zhi-Jie; Zhou, Jia-Rui; Liu, De-Yan; Yang, Jun-Fang; Zhang, Xian; Lu, Dao-Pei; et al. (Frontiers in Immunology, 2023)
Introduction We aimed to evaluate prognostic factors of a second allogeneic stem cell transplantation (allo-HSCT2) among hematological malignancy patients who have relapsed after the first allo-HSCT(allo-HSCT1). Methods We retrospectively analyzed 199 hematological malignancy patients who received allo-HSCT2 as a salvage treatment post allo-HSCT1 relapse between November 2012 and October 2021. Results The median age at allo-HSCT2 was 23 (range: 3-60) years. The median time to relapse after HSCT1 was 9 (range: 1-72) months. Prior to allo-HSCT2, patients had the following hematopoietic cell transplantation-comorbidity indexes (HCT-CI): 127 with a score of 0, 52 with a score of 1, and 20 with a score of 2 or greater. Fifty percent of patients received chimeric antigen receptor (CAR) T-cell therapy following HSCT1 relapse. Disease status was minimal residual disease (MRD)-negative complete remission (CR) among 119 patients, MRD-positive CR among 37 patients and non-remission (NR) for 43 patients prior to allo-HSCT2. Allo-HSCT2 was performed from a new donor in 194 patients (97.4%) and 134 patients (67.3%) received a graft with a new mismatched haplotype. The median follow-up time was 24 months (range: 6-98 months), and the 2-year OS and LFS were 43.8% ± 4.0% and 42.1% ± 4.1%, respectively. The 2-year cumulative incidence of relapse (CIR) and non-relapse mortality (NRM) was 30.0%±4.8% and 38.5%±3.8%, respectively. Cox regression multivariate analysis showed that disease statusof MRD-negative CR, HCT-CI score of 0 prior to allo-HSCT2, and new mismatched haplotype donor were predictive factors of improved OS and LFS compared to patients without these characteristics. Based on these three favorable factors, we developed a predictive scoring system for patients who received allo-HSCT2. Patients with a prognostic score of 3 who had the three factors showed a superior 2-year OS of 63.3% ± 6.7% and LFS of 63.3% ± 6.7% and a lower CIR of 5.5% ± 3.1% than patients with a prognostic score of 0. Allo-HSCT2 is feasible and patients with good prognostic features prior to allo-HSCT2 —disease status of CR/MRD- and HCT-CI score of 0 as well as a second donor with a new mismatched haplotype could have the maximal benefit from the second allo-HSCT. Conclusions Allo-HSCT2 is feasible and patients with good prognostic features prior to allo-HSCT2 —disease status of CR/MRD- and HCT-CI score of 0 as well as a second donor with a new mismatched haplotype could have the maximal benefit from the second allo-HSCT.